Heat kernel, spectral functions and anomalies in Weyl semimetals. (7th June 2022) - Ivanov, A V; Kurkov, M A; Vassilevich, D V
Abstract: Being motivated by applications to the physics of Weyl semimetals we study spectral geometry of Dirac operator with an abelian gauge field and an axial vector field. We impose chiral bag boundary conditions with variable chiral phase θ on the fermions. We establish main properties of the spectral functions which ensure applicability of the ζ function regularization and of the usual heat kernel formulae for chiral and parity anomalies. We develop computational methods, including a perturbation expansion for the heat kernel. We show that the terms in both anomalies which include electromagnetic potential are independent of θ .